A comparison between visible wavelength hyperspectral imaging and digital photography for the detection and identification of bloodstained footwear marks. Issue 6 (7th August 2021) - Crowther, Matthew; Li, Bo; Thompson, Timothy; Islam, Meez
Abstract: One of the first challenges that crime scene examiners have is determining if a substance is blood before performing analysis. Conventional methods of detecting blood involve the use of chemicals and different wavelengths of light in tandem with digital photography. However, these methods are destructive or provide false positives. Visible wavelength hyperspectral imaging (HSI) is a noncontact blood detection method that has been proven to provide accurate and reliable results. A novel application of this technique has been used for the detection and positive identification of bloodstained footwear marks, of different dilutions ranging from undiluted to 1:50 with distilled water, and on a range of substrates, and colors. Comparisons between HSI and conventional digital photography were made using a grading scale and analyzed using Mann‐Whitney U ‐tests. The HSI technique was able to detect a statistically significant greater amount of tread detail on white tiles, laminate, carpet, and blue tiles compared with the digital photography technique, which was only superior on black tiles. Critically, the HSI technique was also able to determine that the footwear marks were made in blood. These results show that HSI will be useful in forensic investigations, where it is known that the perpetrator has walked through the victim's blood and left a trail of footwear marks at the crime scene. Even if the perpetrator had time to clean up afterward resulting in diluted stains, HSI would still be able to detect bloodstained footwear marks with a greater amount of detail compared with digital photography.